Parallel FFT Based Fast Algorithms for Solving Large Scale Electromagnetic Problems - Ming Zhang; Tat Soon Yeo; Le Wei Li; Yeow Beng Gan (2006 IEEE Antennas and Propagation Society International Symposium, 2006)
This paper presents two parallel schemes of fast algorithms based on the parallel FFT. In the first scheme, the parallel FFT is applied to speed up multiplication of the impedance matrix and a vector directly. In the second scheme, the AIM is parallelized. To demonstrate the efficiency of the parallel schemes, electromagnetic scattering by a very large cylindrical wire array and a conducting sphere are computed